THE INFLUENCE OF NET PROFIT MARGIN AND EARNING PER SHARE ON STOCK PRICES IN VARIOUS INDUSTRIAL SECTOR COMPANIES LISTED ON THE IDX FOR THE 2015-2019 PERIOD - Purdianto, Ario; Parlina, Nurhana Dhea; Apriliani, Dini (Transpublika Publisher, 2022)
This research aims to evaluate the impact of Net Profit Margin and Earnings Per Share on the stock prices of IDX-listed manufacturing businesses from 2015 to 2019. The adopted technique of research is quantitative research. This research utilizes net profit margin and profits per share as independent variables. The stock price serves as the dependent variable. The sample for this research consisted of 21 manufacturing companies that were listed on the Indonesia Stock Exchange between 2015-2019 and were chosen using the technique of purposive selection based on certain criteria. The method employed in this research is an SPSS-based multiple linear regression analysis. The t test revealed that the NPM and EPS variables had a positive and statistically significant effect on stock prices. If Net Profit Margin (NPM) increases in value, so does the share price, resulting in a rise in stock prices. Therefore, it can be extrapolated that investors must enhance their ability to comprehend the information provided by the company in annual reports and financial reports. Permits investors to assess the factors that may affect the growth in a company's stock price, the level of risk, and the resulting rate of return. Before investing money, investors might make better decisions if they are well-informed.